The Usage of ‘Turnitin’ as an Innovative Educational Tool: Inculcating Critical Thinking in Integrating Naqli and Aqli for Subject of Malaysian Economy - Fuadah Johari; Mohammad Haji Alias; Asma Abdul Rahman; Mohd Firdaus Ibrahim (Elsevier, 2024)
Volume :195